Effectiveness Of Black Garlic Extract Against Various Organs: A Review - Nora Maulina; Indra Zachreini; Gholib Gholib; Muslim Akmal (Faculty of Medicine University of Malikussaleh, 2022)
Black garlic is a fermented form of garlic (Allium sativum) which is obtained by heating (60-90 ͦ C) and humidity of 70-90% for a certain period of time. Black garlic, which is rich in functional compounds, is certainly very beneficial, especially for several organs in the body, such as cardiovascular, respiratory, hepatobiliary, kidney, gastrointestinal tract organs, and others. The study used is a literature review study using in vitro, in silico research articles and literature review articles. The results showed that the effectiveness of black garlic extract was mainly attributed to its antioxidant, immunomodulatory, anti-inflammatory, digestive system protective, hepatoprotective, cardiovascular protection, neuroprotective, and nephroprotective compou